Fatigue assessment of stern ramps - Jalkevik, Aron; Toresson, Karl (My University, 2013)
RoRo ships are an important ship type in transports at sea today. Reliable designs of their loading ramps are required to ensure the safe and efficient loading and unloading of cargo. Today, most ramps are designed against ultimate strength despite the fact that they are subjected to repeated loading from rolling cargo. The class rules, however, do not take fatigue damage into consideration. In this thesis, two RoRo ramps have been investigated from a fatigue point of view. An existing method for performing fatigue assessment and life estimations is to be modified to suit RoRo ramps in the future. The ramps investigated are a straight stern ramp and a quarter ramp. Two different methods have been used for investigating these ramps. On the straight stern ramp, fatigue damage has been found in the form of cracks in a specific area. Focus has therefore been on investigations of this area. First by stress analyses and subsequently by fatigue analyses based on these stresses. On the quarter ramp no such area is known and therefore a global stress analysis of the ramp has been performed to identify areas with stress concentrations and subsequently sub-models of these areas have been created to get more accurate stress levels in these areas. After the local stresses have been calculated, the stresses are used for estimating the fatigue life of the structure. For the fatigue assessment of the ramps, mainly the stress-based approach has been applied. The number of cycles to failure has been calculated and estimations of the load spectrum were made in order to give an approximation of the fatigue life. In Case Study 1, it was found that the stresses in the ramp were above the yield limit and close to the ultimate strength, which made the estimated fatigue life especially short. In order to perform more accurate lifetime calculations the actual load spectrum needs to be specified. In Case Study 2, a number of potential critical areas was found and sub-models of these areas have been investigated and evaluated from a fatigue point of view. The critical areas have been further investigated with various motivations, for instance high local stresses in the global model and geometry study in order to find local stress concentrations. The stresses obtained in the investigated areas were used to perform fatigue life estimations. In Case 2, it has been shown that the fatigue life was adequate.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering